ANALISIS PENYALURAN KREDIT PENGUSAHA KECIL (KPK) PADA PT. BANK RIAU KEPRI CABANG PEMBANTU AHMAD YANI - Febrian, Acmad Fajri; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aimed to analyze lending small businesses on PT. Bank Riau Kepri, Branch Ahmad Yani, Pekanbaru to see the connection between the guidelines made by PT. Bank Riau Kepri in SK Directors Number: 107 / KEPDIR / 2013 dated October, 2013. The lending process is a series of stages that are integrated end-to-end process, which must be passed interconnectedness starting from initiation (petition), analysis, decision, realization of credit and credit administration stage, until completion non-performing loans. To explore the topics discussed, the researchers conducted interviews with key informance, because this research is qualitative data obtained by conducting interviews directly to the parties concerned, subsequent interpretation associated with the theories related to the process or the execution of lending small businesses (KPK) on PT. Bank Riau Kepri Branch Ahmad Yani, Pekanbaru.The results showed that PT. Bank Riau Kepri Branch Ahmad Yani, Pekanbaru carry out lending in accordance with guidelines issued by PT. Bank Riau Kepri and has been in line with theories of banking in general or regulations of Bank Indonesia on credit. However, in order to maintain the health of banks, PT. Bank Riau Riau, branch assistant Ahmad Yani Pekanbaru should conduct assessment more tightly against the principle of 5C and a feasibility study is mainly Collateral accepted that the rate of return is guaranteed and customers have the motivation to restore credit smoothly, so that the bank can minimize the occurrence of bad loans (non-performing loans).Keywords: credit, credit phases, small businesses loans, non-performing loan